Use of green propolis extract in controlling of anthracnose in 'Palmer' mangoes - Guimarães, J. E.R. [UNESP]; Silva, J. P. [UNESP]; Fernandes, J. D.R. [UNESP]; Marques, K. M. [UNESP]; Galati, V. C. [UNESP]; Muniz, A. C.C. [UNESP]; Mattiuz, B. H. [UNESP] (International Society for Horticultural Science (ISHS), 2017)
The objective of this study was to evaluate the use of propolis associated with carnauba wax on postharvest control of anthracnose in mangoes 'Palmer'. The fruits lat physiological maturity stage, were uniformly wounded (four equidistant injuries) and artificially inoculated with 15 μL of the conidial suspension of Colletotrichum gloeosporioides in concentration 105 con mL-1. The fruits were stored for 10 h at 22°C for fungal establishment. Carnauba wax 12% (Aruá®) was used as coating adding concentrations of 0, 0.5, 1, 1.5, 2 and 2.5% of propolis extract, applied by dipping the fruit (one minute). For each treatment, were used four replicates with two fruits each. After drying and formation of coatings the fruits were stored at 12±2°C and 80±5% RH for 12 days, when they were removed and placed in 25°C for 3 days to simulate marketing. In the experiment were evaluated: weight loss, peel color and pulp firmness, titratable acidity, ascorbic acid, soluble solids and lesion diameter. It was found that treatments with wax and propolis delayed fruit ripening, especially the wax treatment combined with 2% of green propolis showed at the end of the 15th day of storage the smallest diameters of the lesion, demonstrating that green propolis has potential as an alternative fungicide in controlling anthracnose in 'Palmer' mango.
Keywords: Alternative products; Colletotrichum gloeosporioides; Disease; Mangifera indica L.; Quality; Storage